Marine productivity controlled by oceanic circulation in the Northwest Pacific over the last glacial cycle - Hu, Limin; Fang, Hao; Shi, Xuefa; Zhang, Yuying; Duan, Zhifei; Li, Chao; Lippold, Jörg; Ikehara, Minoru; Luo, Yiming (Global and planetary change, 2024)
The oceanic carbon cycles have a significant effect on the climate transitions by influencing the atmospheric CO2 levels. As one of the largest carbon sinks, the Northwest Pacific is the key to understand how the carbon cycles react to past and future climate changes. In this study, the marine productivity in Northwest Pacific over the last 25,000 years has been comprehensively reconstructed using 230Th-normalized biogenic fluxes recorded in a series of sedimentary cores. Our results show contrasting onsets of productivity pulse between cores from the subarctic and the subtropical gyres, while both have been controlled by the nutrient supply related to ocean circulation. Specifically, the wind-driven southward shift of subarctic gyre combined with stronger East Asia winter monsoon during the Last Glacial Maximum and early deglaciation supplied more nutrients to the south and stimulated the subtropical productivity, while this process synchronously limited the subarctic productivity especially with downward extension of the North Pacific Intermediate Water (NPIW). The contraction of subarctic gyre associated with the collapse of the NPIW during the Bølling-Allerød generated the productivity pulse in subarctic region and lowered the subtropical productivity. Terrigenous inputs, reconstructed from 232Th fluxes, however, mainly affected the productivity in the subtropical gyre over the last glacial cycle, especially for the marginal region, in contrast to the pelagic subarctic gyre. Our findings reveal an interplay between subarctic and subtropical gyres and their integrated impacts on marine productivity, providing a paleoceanographic perspective to understand the carbon budget across different timescales in the Northwest Pacific.
Gesehen am 20.08.2025